ORTHODONTIC BRACKET BONDING PERFORMANCE: ASSESSING THE ROLE OF TEMPORARY CROWN MATERIALS AND SURFACE TREATMENT TECHNIQUES - Abdulaziz , Ali Al-Farsi; Al-Mutairi, Sara Abdullah (American Research Journal of Nursing and Health Sciences (ARJNHS), 2023)
In the contemporary digital age, there is a steady rise in the number of adults seeking orthodontic treatment for both esthetic enhancements and oral rehabilitation. Adult patients often present with unique challenges, including missing teeth, multiple restorations, and artificial prosthesis. Typically, final restorations are deferred until the completion of orthodontic treatment, necessitating the bonding of brackets to provisional crowns throughout the orthodontic journey. This practice, however, poses distinct challenges, as studies have indicated that bonding brackets to provisional crowns is more intricate compared to bonding to natural teeth. Furthermore, the provisional crown material must exhibit exceptional physical and mechanical properties, withstand occlusal and orthodontic forces, offer superior handling, boast enhanced esthetics, and demonstrate biocompatibility with oro-dental tissues. This article delves into the various aspects of orthodontic bracket bonding on provisional crowns made from diverse materials. We explore the importance of selecting the appropriate provisional crown material and its impact on the overall success of orthodontic treatment. In addition, we discuss the challenges associated with direct bracket bonding on different provisional crown materials and the critical role of surface treatment in improving bond strength. Our review encompasses traditional materials like polycarbonate and auto-polymerizing polymethylmethacrylate (PMMA) resins, as well as innovative materials such as computer-aided design/computer-aided manufacturing (CAD/CAM) PMMA and bis-acryl resins for provisional crown fabrication